Approaches for enhancing abiotic stress tolerance in plants - Hasanuzzaman, Mirza (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Plants are frequently exposed to unfavorable and adverse environmental conditions known as abiotic stressors. These factors can include salinity, drought, heat, cold, flooding, heavy metals, and UV radiation which pose serious threats to the sustainability of crop yields. Since abiotic stresses are major constraints for crop production, finding the approaches to enhance stress tolerance is crucial to increase crop production and increase food security. This book discusses approaches to enhance abiotic stress tolerance in crop plants on a global scale. Plants scientists and breeders will learn how to further mitigate plant responses and develop new crop varieties for the changing climate.
OCLC-licensed vendor bibliographic record.
Keywords: Plants -- Effect of stress on; SCIENCE / Life Sciences / Botany; SCIENCE / Environmental Science; TECHNOLOGY / Agriculture / General